2006
DOI: 10.1111/j.1467-9450.2006.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

The possible benefits of difficulty: How stress can increase and decrease subjective well‐being

Abstract: This study explores the effects of stress, trauma, coping and growth orientation on subjective well-being. Based on cognitive stress theory, it was hypothesized that adversity may contribute to increased or decreased well-being, depending on the subsequent meaning these experiences are given. Survey data from Norwegian UN/NATO veterans (N= 142) showed that stress and well-being were negatively associated (r=-0.20, p < 0.05) at the level of zero-order correlations. However, a full structural equation model reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 38 publications
(42 reference statements)
0
18
0
7
Order By: Relevance
“…Some theorists argue that a moderate amount of challenge, struggle, burden, and negative affect can be positive and necessary for human development and to achieve a deeper and more permanent sense of well-being (Karlsen et al 2006;Vittersø 2004).…”
Section: [Table 1 About Here]mentioning
confidence: 99%
“…Some theorists argue that a moderate amount of challenge, struggle, burden, and negative affect can be positive and necessary for human development and to achieve a deeper and more permanent sense of well-being (Karlsen et al 2006;Vittersø 2004).…”
Section: [Table 1 About Here]mentioning
confidence: 99%
“…In addition, a number of studies have found that posttraumatic growth correlates positively with adverse reactions to war-related trauma (i.e., symptoms of PTSD) in both veterans (Dekel, Ein-Dor, & Solomon, 2012;Kaler, Erbes, Tedeschi, Arbisi, & Polusny, 2011;Karlsen, Dybdahl, & Journal of Clinical Psychology, April 2015Vittersø, 2006Levine, Laufer, Stein, Hamama-Raz, & Solomon, 2009;Pietrzak et al, 2010) and civilians (e.g. refugees; Dekel & Nuttman-Shwartz, 2009;Hall et al, 2010;Hobfoll et al, 2008).…”
Section: Posttraumatic Growth and War-related Traumamentioning
confidence: 99%
“…The studies of Vittersø and colleagues [ 66 , 67 ] confirmed that happiness scores were higher in easy episodes while interest was higher in difficult episodes. Happiness was higher before work on a Sudoku puzzle than during the work.…”
Section: Introductionmentioning
confidence: 97%